2016
DOI: 10.1213/ane.0000000000001237
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Falls After Total Knee Arthroplasty with the Use of a Femoral Nerve Block Versus an Adductor Canal Block: A Double-Blinded Randomized Controlled Study

Abstract: ACB results in greater preservation of quadriceps muscle strength. Although we did not detect a significant reduction in fall risk when compared with FNB, based on the upper limit of the relative risk, it may very well be present. Further study is needed with a larger sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
126
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 38 publications
2
126
1
1
Order By: Relevance
“…Another 3 studies were identified through manual search. After removing duplications, scanning titles and abstracts, and reading the full-text, 12 RCTs met the inclusion criteria151617181920232425313233.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 3 studies were identified through manual search. After removing duplications, scanning titles and abstracts, and reading the full-text, 12 RCTs met the inclusion criteria151617181920232425313233.…”
Section: Resultsmentioning
confidence: 99%
“…Several more RCTs on this subject have been published without conclusive results20232425. In addition, Li et al .…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] However, controversy exists regarding the ideal location of ACB placement within the adductor canal. A more proximal ACB may offer improved analgesia and a more remote insertion site away from the surgical field; however, the proximal block may produce greater quadriceps weakness by targeting several afferent branches of the femoral nerve.…”
mentioning
confidence: 99%
“…In recent years, considerable efforts have been deployed to develop quadriceps-sparing nerve blocks for total knee replacement. 7 Inexplicably, diaphragm-sparing blocks for shoulder surgery have received less attention. 8 This unfortunate situation needs remedy, as HDP can be as deleterious as quadriceps paralysis.…”
mentioning
confidence: 99%